PENDAMPINGAN PENERAPAN VALUE CLARIFICATION TECHNIQUE UNTUK PENGUATAN KOMPETENSI GURU DALAM PEMBELAJARAN KARAKTER DI SEKOLAH DASAR - Hariyadi, Sigit; Kunwijaya, Indrajati; 'Ilmi, Achmad Miftachul; Mulyani, Petra Kristi; Kurniawan, Kusnarto; Hartati, Maria Theresia Sri; Azhar, Nailah Rizqia; Setiyawati, Dewi Ayu; Suhur, M. Khautalfata; Seto, Mustofa Danu (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Character education in elementary schools remains a challenge, particularly with regard to students’ low level of social awareness, the emergence of bullying behavior, and the suboptimal internalization of values such as empathy and tolerance. These conditions indicate limitations in pedagogical approaches to character education that have not yet systematically engaged students in value reflection processes. This community service program aimed to enhance the pedagogical competence of elementary school teachers in implementing character education based on the Value Clarification Technique (VCT). The program was conducted in Sambirejo Village, Semarang Regency, involving 16 teachers from two elementary schools as partner institutions. The service employed a participatory training and mentoring approach, including needs analysis, VCT workshops, mentoring during classroom implementation, and evaluation. Data were collected through pre- and post-tests of teachers’ understanding, observations of instructional practices, and reflective mentoring notes, and were analyzed using descriptive statistics and qualitative analysis. The results indicate an improvement in teachers’ understanding of VCT concepts and implementation steps, changes in instructional practices toward more dialogical and reflective learning, and improvements in classroom dynamics characterized by increased empathy, mutual respect, and students’ prosocial behavior. These findings demonstrate that VCT-based mentoring is effective in strengthening character education in elementary schools and contributes to the development of a child-friendly and character-oriented school culture.